Analysis of Distance Learning Implementation at Elementary School Sengon 2 Trenggalek - Samsirin Samsirin; Arya Fredo Ramadhani; Agung Purnomo Djati (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
This study aims to analyze and describe the implementation of distance learning, as well as determine the supporting and inhibiting factors for the implementation of distance learning at SDN Sengon 2 Trenggalek. This type of research is qualitative research with descriptive methods. Participants in this study were the principal, teachers, and parents or guardians of students. Data were collected by means of observation, interviews and documentation. The results of this study are described as follows: 1) Distance learning at SDN Sengon 2 Trenggalek is carried out using online and offline methods, the strategy adopted by the teacher is to use technology with PJJ media via Study group. 2) Supporting factors for the implementation of distance learning, namely teachers prepare careful planning in implementing PJJ, the support of internet facilities from schools, and teachers and parents can use technology for communication without any time constraints. The inhibiting factor for the implementation of distance learning is that most parents cannot always assist students in learning because they have jobs that cannot be left behind, assignments given by the teacher require more explanation, and students' learning motivation decreases.